Uji Kinerja Alat Kastrasi Modifikasi Bambu pada Areal Tanaman Belum Menghasilkan PT. Sawit Sejahtera - Steven Saputra Jaya Sirait; Tarmadja, Samsuri; Ardiani, Fani (AGROISTA : Jurnal Agroteknologi, 2025)
This research was conducted at PT. Sawit Sejahtera, South Sumatra Province, from February to April 2024. This study aimed to assess and test the effectiveness of castration tools by comparing 8 cm dodos with modified bamboo tools for castration on immature oil palm plants. This study used a survey method to describe the research location and collect primary data. The research was conducted in Block E-01, which has a hilly area. Each tool was tested on 150 sample trees located on 10 different terraces. The data observed included worker output, work quality, and safety risks. Data were analyzed using an independent t-test. The results showed that the use of the modified bamboo tool for castration was generally more effective as it produced 15.71% higher worker output compared to the dodos tool. Work quality was also better with the bamboo tool, as no fronds were damaged in the sample trees, while 126 trees or 84% of the sample trees were damaged due to the dodos tool. However, in terms of safety, no accidents were reported from using either tool. Nonetheless, the tool's effectiveness comes with the note that castration must be performed monthly.